La enfermedad holandesa y la minería en el Perú en el período de 1995: T1 - 2015: T4 - Alayo Paytan, Dina Patricia (2016)
Present research aims to determine whether the behavior of the mining sector has led to the presence of Dutch disease in Peru, 1995 period: T1-2015: T4. For which the approach and experimental investigation Slitting was used. The research is a correlational scope as it aims to understand the relationship between the study variables for which the information collected in the theoretical framework was used. Real exchange rate, gold price, fiscal deficit, terms of trade, real GDP and Indicator deindustrialization: To reach the results methodology autoregressive models (VAR), which included the following variables were used. Finally it got the boom in the mining sector in Peru, if you have generated the presence of Dutch disease.